2017
DOI: 10.1016/j.socscimed.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Predictive utility and measurement properties of the Strength of Implementation Intentions Scale (SIIS) for condom use

Abstract: Background Implementation intentions are situation-linked action plans that increase health behaviors such as condom use. Few studies have measured the strength of implementation intentions, especially regarding condom use. Non-injection drug users are at high risk for HIV due to risky sexual practices. Substance use before sex may increase risky sexual behaviors, and implementation intentions are a promising, practical route for HIV prevention. Purpose This prospective study assessed the measurement propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 51 publications
2
14
0
3
Order By: Relevance
“…The majority of included studies reported measurement properties of instruments that assessed acceptability ( n = 33) [ 23 59 ], followed by appropriateness ( n = 7) [ 46 , 60 – 65 ], adoption ( n = 4) [ 66 69 ], feasibility ( n = 4) [ 46 , 70 , 71 , 80 ], penetration ( n = 4) [ 72 75 ] and sustainability of evidence-based practice (intervention or service) ( n = 3) [ 76 79 ]. No studies of intruments measuring implementation cost were identified (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of included studies reported measurement properties of instruments that assessed acceptability ( n = 33) [ 23 59 ], followed by appropriateness ( n = 7) [ 46 , 60 – 65 ], adoption ( n = 4) [ 66 69 ], feasibility ( n = 4) [ 46 , 70 , 71 , 80 ], penetration ( n = 4) [ 72 75 ] and sustainability of evidence-based practice (intervention or service) ( n = 3) [ 76 79 ]. No studies of intruments measuring implementation cost were identified (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies assessing implementation outcome measures has increased over time, with one study published in 1998 [ 79 ], through to eight studies published in 2018/2019 [ 27 , 42 , 45 , 49 , 56 , 62 , 76 , 77 ]. Studies were predominantly conducted in high-income countries, with the majority conducted in the USA alone ( n = 22) [ 25 , 29 , 30 , 35 , 37 39 , 44 , 46 , 47 , 53 , 57 , 58 , 64 , 66 , 67 ]. A small number of studies were conducted in lower-middle-income countries (LMIC), namely Brazil [ 31 , 60 ] and Iran [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation intentions involve an “if-then strategy,” for example, “If it is 4 pm, I will go to the gym” ( Armitage, 2016 ; Gollwitzer, 1999 ; Hagger and Luszczynska, 2014 ). In a study of condom use among non-injecting drug users, implementation intentions (“I have detailed plans of what I will say if my partner refuses to use a condom.”) had a greater impact than simple behavioral intentions (“I intend to use a condom.”; Nydegger et al, 2017 ). As noted earlier, in one study of college-age participants, those who reported intending to limit their drinking over the weekend showed the most responsiveness to the text messaging program over a 12-week period as compared with those who did not intend to limit their drinking ( Suffoletto and Chung, 2016 ).…”
Section: Discussionmentioning
confidence: 99%